TRAINING OF HOME PRODUCT ENTREPRENEURS TO INCREASE FAMILY INCOME IN RW 03 GUNUNG BATU URBAN VILLAGE, WEST BOGOR - Cucu Sumartini, Lilis (LPPM Univ. Ibn Khaldun Bogor, 2022)
Home production is one of the activities that can generate money and can increase family income or income. The right production and marketing will produce large profits. Big profits will automatically increase revenue. Training is an activity that can provide knowledge and insight into the production process and marketing. Training is carried out using the lecture method. The results of the training are expected to increase production and increase sales volume. This causes profits to rise. If sales increase, it will increase revenue.